PENGARUH PENCAMPURAN KOTORAN TERNAK SEBAGAI MEDIA KULTUR TERHADAP PERTAMBAHAN POPULASI CACING TANAH (Lumbricus rubellus) - Satria Edi Putra; Iskandar Johan; Muhammad Hasby (UIR Press, 2018)
This research aims to determine the effect of mixing cattle dung as a culture medium to the growing population of earthworms. The research was conducted for 42 days starting from 18 October to 28 November 2017 at the fish farming school hall of Agriculture Faculty of Islamic University Riau Pekanbaru. The worm tree used in this study was as many as 960 tail or 80 tail for each container. Worms are maintained for 42 days with different mixtures of medium, i,e, 100% P1 dung treatment, P2 cow-dung treatment 50% + 50% buffalo dung, 50% cow dung + 50% goat dung, 50% cow dung + 50% chicken droppings. The research design was Completely Randomized Design with 4 treatments and 3 replications. The result of this research showed that the increase of population of earthworm with the mixing of cattle dung as culture media which conducted for 42 days is the best treatment of P2 as much as 4266 head/container, then the second one used was in treatment 3 as much as 1855 head/container, and the lowest increase of the population was at treatment P1 as much as 403 head/container, and followed by treatment P4 as much as 575 head/ container.